REDUCING THE PRODUCT CHANGEOVER TIME USING SMED & 5S METHODS IN THE INJECTION MOLDING INDUSTRY - Daniel Agung; Hasbullah Hasbullah (Universitas Mercu Buana, 2019)
Along with the increasing market of plastic packaging products resulting from the injection process and the rapid development of existing technology, we need a strategy to be able to continue to meet the customer’s needs and to be able to compete in the industry. One of the strategies that may be employed is Lean. Lean is a concept aimed at eliminating existing waste. One of the implementations of Lean’s concept is the SMED (Single Minute Exchange of Dies) concept. SMED is a concept aimed at reducing the changeover time, so the eliminated time can be used in the production process. P.T. BIL is one of the companies engaged in the production of plastic packaging with an injection process. Problems occurring at P.T. BIL was the absence of a measurement process for changeover time. The Operation Analysis Chart concept was used to analyze the carried-out activities. To optimize activities employing the SMED concept, Analytical Cards were used so that the change over time can be reduced. The 5S concept was applied to support the SMED concept, so the waste in the work area could be eliminated. By implementing the SMED concept, we reduced 18% of the change over time.